Generic Energy Matching Model and Figure of Matching Algorithm for Combined Renewable Energy Systems - S. Y. Kan; J.C. Brezet (Journal of Systemics, Cybernetics and Informatics, 2009)

(untitled)
In this paper the Energy Matching Model and Figure of Matching Algorithm which originally was dedicated only to photovoltaic (PV) systems [1] are extended towards a Model and Algorithm suitable for combined systems which are a result of integration of two or more renewable energy sources into one. The systems under investigation will range from mobile portable devices up to the large renewable energy system conceivably to be applied at the Afsluitdijk (Closure- dike) in the north of the Netherlands. This Afsluitdijk is the major dam in the Netherlands, damming off the Zuiderzee, a salt water inlet of the North Sea and turning it into the fresh water lake of the IJsselmeer. The energy chain of power supplies based on a combination of renewable energy sources can be modeled by using one generic Energy Matching Model as starting point.